Oosporein, an abundant metabolite in Beauveria caledonica, with a feedback induction mechanism and a role in insect virulence. Issue 8 (August 2019) - Mc Namara, Louise; Dolan, Stephen K.; Walsh, John M.D.; Stephens, John C.; Glare, Travis R.; Kavanagh, Kevin; Griffin, Christine T.
Abstract: Oosporein was first identified from the insect pathogen Beauveria bassiana >50 y ago. Here, we investigate the insecticidal, anti-feedant and immunomodulation effects of oosporein produced by Beauveria caledonica on the forestry pest Hylobius abietis and model insect Galleria mellonella . We report a novel feedback induction mechanism regulating oosporein production in B. caledonica; exogenous oosporein induces the expression of the oosporein cluster, leading to increased abundance of oosporein biosynthetic enzymes, as shown by label-free quantitative proteomics. Oosporein did not have an anti-feedant effect on H. abietis adults – on the contrary, insects exposed to oosporein-treated food fed more than those exposed to untreated food only. Injected oosporein did not kill insect larvae but increased susceptibility of H. abietis to a subsequent infection. Oosporein did not act as a contact toxin on H. abietis adults and G. mellonella larvae at the concentrations tested. Therefore, it appears that oosporein promotes infection rather than directly killing insects; this could be mediated both by a reduction in haemocyte numbers and by alterations to the humoral immune system. This work makes a case for future research into the potential use of B. caledonica as a biocontrol agent through combinations with oosporein or with enhanced production of oosporein. Highlights: Oosporein is produced by Beauveria caledonica . Oosporein exhibits immunomodulation properties. Oosporein promotes infection rather than directly killing insects. A feedback induction mechanism regulates oosporein production in B. caledonica .